2019
DOI: 10.1016/j.soard.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of childhood trauma on change in depressive symptoms, eating pathology, and weight after Roux-en-Y gastric bypass

Abstract: Background: History of childhood trauma is associated with increased risk of mental disorders, eating pathology and obesity. Objective: To examine associations between childhood trauma and changes in depressive symptoms, eating pathology and weight following Roux-en-Y Gastric Bypass (RYGB). Setting: Three U.S. academic medical centers. Method: Adults undergoing bariatric surgery (2007-2011) were enrolled in a cohort study. Participants (96 of 114; 86%) completed the Beck Depression Inventory-1 (BDI-1) to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
(61 reference statements)
1
13
0
Order By: Relevance
“…Although some investigators have postulated that being a victim of childhood sexual abuse may impact the weight loss outcome of bariatric surgery, because weight may be protective for survivors of childhood sexual abuse, results of studies have been mixed . A recent LABS‐3 cohort study that included 96 patients undergoing bariatric surgery with ≥ 7 years of follow‐up found that history of childhood sexual abuse was not significantly related to weight loss or regain following RYGB . History of childhood sexual abuse may be associated with increased risk of psychiatric hospitalization after bariatric surgery .…”
Section: Bariatric Population Mental Health Risksmentioning
confidence: 99%
“…Although some investigators have postulated that being a victim of childhood sexual abuse may impact the weight loss outcome of bariatric surgery, because weight may be protective for survivors of childhood sexual abuse, results of studies have been mixed . A recent LABS‐3 cohort study that included 96 patients undergoing bariatric surgery with ≥ 7 years of follow‐up found that history of childhood sexual abuse was not significantly related to weight loss or regain following RYGB . History of childhood sexual abuse may be associated with increased risk of psychiatric hospitalization after bariatric surgery .…”
Section: Bariatric Population Mental Health Risksmentioning
confidence: 99%
“…34 Patients with unresolved trauma are more likely to present after bariatric surgery with difficulties, for example, increased alcohol use; unhealthy eating behaviors; poor weight-loss; and increased suicide risk. [36][37][38][39] The use of food as an emotional regulatory strategy, and as a method of self-soothing has been postulated as an explanatory mechanism. 32 Although there are improvements in cognitive function postbariatric surgery for those with pre-surgical severe and complex obesity, there is a correlation between elevated levels of disinhibition and lower levels of restraint with poor compliance with post-surgical dietary recommendations and suboptimal weight loss 2 years after surgical intervention.…”
Section: What Are the Increased Risks For Those Who Have Had Bariatri...mentioning
confidence: 99%
“…Further, childhood sexual abuse is cited as having the greatest impact on living with childhood obesity in comparison to other Adverse Childhood Experiences (ACEs), with multiple ACEs predicting increased risk 34 . Patients with unresolved trauma are more likely to present after bariatric surgery with difficulties, for example, increased alcohol use; unhealthy eating behaviors; poor weight‐loss; and increased suicide risk 36–39 . The use of food as an emotional regulatory strategy, and as a method of self‐soothing has been postulated as an explanatory mechanism 32 …”
Section: Introductionmentioning
confidence: 99%
“…Most research examining the relationship between childhood abuse and obesity treatment has focused on bariatric surgery. Despite some evidence indicating that exposure to adverse childhood experiences, including abuse, is associated with less weight loss following bariatric surgery (10), these findings have been mixed, with additional research showing no relationship between adverse childhood experiences and postoperative weight loss or regain (11).…”
Section: Introductionmentioning
confidence: 99%
“…childhood experiences, including abuse, is associated with less weight loss following bariatric surgery (10), these findings have been mixed, with additional research showing no relationship between adverse childhood experiences and postoperative weight loss or regain (11).…”
mentioning
confidence: 99%